2011
DOI: 10.1016/j.regpep.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretic peptide system: A link between fat mass and cardiac hypertrophy and hypertension in fat-fed female rats

Abstract: The present study was designed to develop an animal model of hypertension and cardiac hypertrophy associated with obesity in female rats. Furthermore, we studied the involvement of the natriuretic peptide system in the mechanisms of these conditions. Obesity was induced in Wistar rats by a high fat diet and ovariectomy. The rats were divided into four groups: ovariectomized or sham-operated with high-fat diet and ovariectomized or sham-operated with control diet. After 24 weeks of diet, rats were killed, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Previous studies on the morphological development of cardiac hypertrophy in this model have been shown previously by our group [ 21 ]. With the onset of cardiac remodeling, both cells and the macroscopic structure of the myocardium undergo functional and morphological changes.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies on the morphological development of cardiac hypertrophy in this model have been shown previously by our group [ 21 ]. With the onset of cardiac remodeling, both cells and the macroscopic structure of the myocardium undergo functional and morphological changes.…”
Section: Resultsmentioning
confidence: 84%
“…After the procedure of ovariectomy, the rats received the following diets: a diet containing 54.4% of total calories from fat (Pragsoluções Biosciences, São Paulo, SP, Brazil) or a control diet or standard diet AIN 93 (Pragsoluções Biosciences, São Paulo, SP, Brazil). The specific compositions of the diets have been reported in a previous study [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When analyzing ANP immunocontent in the RV, an increase in SM group was found, suggesting that, even with no differences in the rate of hypertrophy, it may have a distinct signalling for right ventricular hypertrophy in both groups. It has been shown that estrogen can modulate the ANP release, synthesis and gene expression . According to Kilic et al .…”
Section: Discussionmentioning
confidence: 99%
“…In adipocytes, the levels of NPRC are dynamically regulated in response to nutritional and hormonal status. In obese humans and rodent models, the levels of NPRC are elevated in adipose tissue (9,(13)(14)(15)(16)(17)(18). This is of physiological significance because it has been proposed that greater removal of NPs from circulation by NPRC in adipose tissue could explain what has been referred to as a 'natriuretic handicap' linking obesity and hypertension (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%